Development of the 10-question household foodwork interactional assessment questionnaire (FIA-Q10) - Leah E. Cahill; Sharon I. Kirkpatrick; Catherine L. Mah; Jennifer LP. Protudjer; Cynthia Kendell; Mary E. Jung; Helen Wong; Ellen T. Crumley; Meghan Day; Karen T. Y. Tang; Yan Huang; Jyoti Sihag; et al. (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background Public health nutrition recommendations and clinical dietary interventions emphasize eating healthy food at home, implicitly requiring household foodwork. Household foodwork is defined as the physical and mental tasks a household does for eating meals and snacks. Because no tools exist to measure it, how much time people spend doing household foodwork and the foodwork barriers they experience remain unknown. The objective of the present research was to develop the first stand-alone household foodwork assessment tool. Methods Through informal interviews with partners with lived experience, clinicians, and researchers, a literature review, a stakeholder meeting of advisors, and a two-round electronic Delphi process including face/content validation by expert panelists (n = 21), we developed the 10-question household foodwork interactional assessment questionnaire (FIA-Q10). An optional accompanying module was developed to collect self-identified demographic data to provide context for understanding how social-structural positionality factors may interact to influence foodwork. Results The FIA-Q10 assesses the domains of household composition, frequency of eating at home, special diets within a household, foodwork stress intensity, foodwork barriers, desired supports related to foodwork, and time use for foodwork. The FIA-Q10 measures time use for four subdomains of foodwork among individuals and their households: (1) planning, (2) getting, (3) preparing/cooking, and (4) cleaning up food. In the second Delphi round, the FIA-Q10 scored 95% for language appropriateness, 67% for visual appropriateness, 95% for relevance, 95% for representativeness, and 95% for distribution. Suggested improvements were implemented. All Delphi panelists (100%) reported they would consider using the FIA-Q10. Conclusions The FIA-Q10’s development is the first step towards a standardized assessment of foodwork, enabling examination of challenges in foodwork that may impact nutrition and nutrition equity. Future research will focus on FIA-Q10 validation in multiple populations.